Formulasi Kebijakan Peraturan Daerah Bagi Penyandang Disabilitas Di Kabupaten Bulukumba - Rahmayuni, Yuyu; Usman, Jaelan; Rahim, Samsir (Universitas Muhammadiyah Makassar, 2021)
This study aimed to find out the elite model in the formulation of policies for persons with disabilities ini Bulukumba district. This study used I qualitative research and descriptive research and descriptive type. The number of informants in this study was 10 people. Source of data used primary data and secondary data. Data collection techniques used observation, interviews, and documentation. The results of this study showed that people with disabilities special needs, and in terms of bureaucratic services and access to disability also had not been implemented optimally. The Bulukumba Regency DPRD was a actor who fights as an initiator in the formulation of a Perda for persons with disabilities in Bulukumba Regency. This initiation was obtained from the aspirations of people with disabilities who complained about the various services and infrastructure available in Bulukumba Regency. The positive respons from the DPRD was manifested in concrete actions to draw up a draft regional regulation for persons with disabilities in Bulukumba Regency.